Adenomyosis: correlating clinical suspicion with histopathological diagnosis in a retrospective study - Kamal, Preet; Bala, Ripan; Nagpal, Madhu; Kaur, Harleen (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Adenomyosis and leiomyoma are the common causes of abnormal uterine bleeding (AUB). In this study it is aimed to evaluate the correlation of clinical and histopathological examination (HPE) of these entities leading to abnormal uterine bleeding. Methods: This retrospective study was carried out on hysterectomy specimens of subjects who presented themselves in the department of obstetrics and gynaecology of Sri Guru Ram Das Institute of medical sciences and research, Amritsar with chief complaints of AUB not responding to conservative treatment. Results: A total of 100 women with clinical diagnosis of AUB in which hysterectomies were performed, leiomyoma was found in 42% cases, adenomyosis in 22% cases. The most frequent combination of diagnosis was leiomyoma and adenomyosis i.e. 26%. In 9% cases chronic cervicitis and ovarian cyst were detected. In one case endometrial malignancy was found. Conclusions: Though adenomyosis and leiomyoma are clinically diagnosed along with other pathological conditions of the reproductive organs but their confirmation is still to be relied upon HPE; a most important investigation.